Decolonizing the Child Language Curriculum for Speech-Language Pathologists: A Framework for Transformative Practice - Mershen Pillay; Sarah Spencer; Aydan Suphi; Lindsey Thiel; Dharinee Hansjee; Harsha Kathard (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: Speech and language therapy education has traditionally relied on Euro-American-centric theories of child development. This tutorial examines how child language acquisition curricula can be transformed through decolonization frameworks to better prepare practitioners for culturally responsive practice. Method: Drawing on critical conversations methodology and international collaborative experiences across the United Kingdom, New Zealand, and South Africa, we propose practical recommendations for curriculum transformation that center Indigenous knowledge systems, embrace multilingualism as normative, and develop critical consciousness among educators and students. The tutorial emphasizes shifting from individual deficit models toward community-based, culturally grounded approaches to understanding children's communication development. Case studies illustrate implementations of decolonized practices in university and community settings. Conclusion: This work addresses systemic inequities in speech-language therapy education and practice by providing practical guidance for curriculum transformation while acknowledging that decolonization represents an ongoing, experimental process rather than an outcome.